2019
DOI: 10.1038/s41419-019-2002-6
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome restoration to activate podocyte autophagy: a new therapeutic strategy for diabetic kidney disease

Abstract: Autophagy, the intracellular lysosomal degradation process plays a pivotal role in podocyte homeostasis in diabetic kidney disease (DKD). Lysosomal function, autophagic activity, and their actions were investigated in vitro and in vivo. We found that LC3-II- and p62-positive vacuoles accumulated in podocytes of patients with DKD. Moreover, we found that advanced glycation end products (AGEs) could increase the protein expression of LC3-II and p62 in a dose- and time-dependent manner in cultured podocytes. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 50 publications
4
54
0
Order By: Relevance
“…Obesity or diabetes can lead to impairment of autophagy flux in renal cells [153,154]. HFD/obesity-induced autophagy impairment has been described in rodent models and obese patients [27,155].…”
Section: Ampk and The Regulation Of Renal Autophagy And Mitophagymentioning
confidence: 99%
“…Obesity or diabetes can lead to impairment of autophagy flux in renal cells [153,154]. HFD/obesity-induced autophagy impairment has been described in rodent models and obese patients [27,155].…”
Section: Ampk and The Regulation Of Renal Autophagy And Mitophagymentioning
confidence: 99%
“…P62 is a selective substrate of autophagy, binding directly to LC3 region or ubiquitylated organelles or proteins and p62 expression decline upon autophagy induction. 17 In the study, a weaker LC3-I/II expression of podocytes was shown in IMN patients with higher levels of proteinuria (Proteinuria-H patients, ≄3.5 g/d) than in patients with low levels of proteinuria (<3.5 g/d) by IHC assay ( Figure 1A). In addition, the podocyte LC3B-II dots were decreased and p62 expression was increased in Proteinuria-H patients, in contrast to Proteinuria-L patients viewed by confocal microscopy ( Figure 1B).…”
Section: Serum Spla2-ib Levels and Podocyte Autophagy In The Kidneymentioning
confidence: 64%
“…The results of this study also reveal that autophagy was significantly induced by inhibition of STK25 signaling in human kidney cells, which we observed both in basal culture conditions and when cells were challenged by oleic acid. Autophagy has been demonstrated to play an essential role in protecting the renal cells against injury under diabetic conditions through removal of protein aggregates and damaged organelles as well as by promoting cell survival, and the activation of autophagy has recently been suggested as a potential new therapeutic strategy for DKD (26,(48)(49)(50)(51). Autophagy is thought to be especially important for maintaining the homeostasis of postmitotic cells, such as podocytes, which have only limited capacity for regeneration and display a high level of basal autophagy (27,(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%